2022
DOI: 10.1002/acr.24720
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and Antiphospholipid Syndrome in Israel

Abstract: Objective. Antiphospholipid syndrome (APS) is an acquired coagulopathy associated with the presence of antiphospholipid antibodies. Whether ethnicity modulates APS clinical course is not known. The aim of our study was to assess the interplay of ethnicity and APS in Israel.Methods. We retrospectively evaluated the ethnic distribution of APS patients from 3 medical centers in Israel compared to the general population. Ethnic groups were defined according to the Israeli Bureau of Statistics as Ashkenazi (Europea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The lack of specific information on the race and ethnicity of the patients is another limitation. Data evaluating whether race and ethnicity affect the prevalence of APS are scarce; however, few studies have suggested that they play a role [ 23 , 24 ]. All our participants were from a single center in Denmark and were expected to be predominately Caucasian.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of specific information on the race and ethnicity of the patients is another limitation. Data evaluating whether race and ethnicity affect the prevalence of APS are scarce; however, few studies have suggested that they play a role [ 23 , 24 ]. All our participants were from a single center in Denmark and were expected to be predominately Caucasian.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical variability in PAPS makes it challenging to accurately estimate the incidence and prevalence of this disease in different populations [4]. Despite this, population-based studies report a higher prevalence of PAPS, as well as a higher mortality, in Asian populations [48]. It is noteworthy that possible variability in the strength of genetic associations at the detected loci between populations might affect the accuracy of interpreting these results.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that Japanese APS patients tend to have more arterial events than Europeans, while the latter group is more prone to suffer venous events (estimated prevalence: 23.4 vs. 38.9%, respectively). 59 In an Israeli study, 60 Arab patients, compared to the other ethnicities studied (Asians and Ashkenazi Jews), were younger and more prone to venous thrombosis recurrence (46 vs. 16%), though mortality was higher in the Asian group (8.8 vs. 1.1%). In a Spanish cohort, 61 a higher prevalence of APS was found in Roma SLE patients compared to Caucasians, highlighting a higher prevalence of abortions in the former group.…”
Section: Thrombosis In Apl Carriers and Aps Patientsmentioning
confidence: 98%